Challenge and strategy of 5G radio optimization - Jun ZHOU; Xiao QUAN; Jianhui MA (Dianxin kexue)
The era of network convergence,terminal and business diversification in 5G stage is coming.The radio network will have the situation of coexistence of GSM/TDD/FDD/NB/pre5G/5G/WLAN multi-mode and 900 MHz/1 800 MHz/ F/D/E/A6-band 15 frequency points.Due to the layered service carrying,the existing 4G and 5G interact with each other,which needs to be taken into account.The network structure will be unprecedented complex,and the wireless optimization work situation will be severe.The difficulties and challenges of 5G radio optimization were analyzed,and the strategies to deal with 5G radio optimization was put forward.